Pengaruh CAR, NPL, BOPO, dan LDR Terhadap Profitabilitas Pada PT Bank Lampung Tbk Teluk Betung Periode 2010 2014 - Reviyana Reviyana; Lestari Wuryanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2016)
This research was conducted by PT Bank Lampung Tbk Teluk Betung the period 2010-2011. research to determine the effect of the Capital Adequacy Ratio (CAR), Non Performing Loan(NPL), Operating Expenses to Operating Income (ROA) and Loan to Deposit Ratio (LDR) toprofitability (ROA) with a sample of 20 financial statements quarterly. Solving problems usingmultiple linear regression analysis technique. The results of calculations by t test (partial regressionimpact on profitability (ROA). This is shown from the results of statistical analysis t (1.893) > t table(1.734), the NPL has no significant effect on profitability (ROA). This is shown from the results ofstatistical analysis t (0.526) < t table (1.734), BOPO positive and significant impact on profitability(ROA). This is shown from the results of statistical analysis t (1.974) > t table (1.734), and LDR positiveand significant impact on profitability (ROA). This is shown from the results of statistical analysis tcount (2.203) > t table (1.734). The results of calculations by F test (simultaneous regression test) with-significant effect on profitability (ROA) at PT Bank Lampung Tbk. This is shown from the results of astatistical analysis of F count (4.206) > F table (3.06).